Updated guideline for the management of upper respiratory tract infections in South Africa: 2008 - A.J. Brink (South African Family Practice)
Introduction: Inappropriate use of antibiotics for non-severe upper respiratory tract infections (URTIs), many of which are viral, adds to the burden of antibiotic resistance. Antibiotic resistance is increasing in Streptococcus pneumoniae, the microorganism responsible for most cases of acute otitis media (AOM) and acute bacterial sinusitis (ABS).